Innate lymphocytes: Role in alcohol-induced immune dysfunction - Ruiz-Cortes, Karla; Villageliu, Daniel N.; Samuelson, Derrick R. (Frontiers in Immunology, 2022)
Alcohol use is known to alter the function of both innate and adaptive immune cells, such as neutrophils, macrophages, B cells, and T cells. Immune dysfunction has been associated with alcohol-induced end-organ damage. The role of innate lymphocytes in alcohol-associated pathogenesis has become a focus of research, as liver-resident natural killer (NK) cells were found to play an important role in alcohol-associated liver damage pathogenesis. Innate lymphocytes play a critical role in immunity and homeostasis; they are necessary for an optimal host response against insults including infections and cancer. However, the role of innate lymphocytes, including NK cells, natural killer T (NKT) cells, mucosal associated invariant T (MAIT) cells, gamma delta T cells, and innate lymphoid cells (ILCs) type 1–3, remains ill-defined in the context of alcohol-induced end-organ damage. Innate-like B lymphocytes including marginal zone B cells and B-1 cells have also been identified; however, this review will address the effects of alcohol misuse on innate T lymphocytes, as well as the consequences of innate T-lymphocyte dysfunction on alcohol-induced tissue damage.